Pengaruh Daun Bayam Merah Amarantanthus tricolor L sebagai Material Bioscreen Anti-radiasi pada Laptop - Muslimah Susilayati (Tadris Biologi, Tadris Fisika and Tadris Kimia, Universitas Islam Negeri Antasari, 2022)
The era of the industrial revolution 4.0 and society 5.0 has necessitated the use of technology in life. For academics, the use of technology is very dependent on laptops. The use of laptops for various purposes is increasing. However, the electromagnetic radiation emitted by laptops can harm the wearer. Reducing radiation on laptops can be pursued through the use of environmentally friendly renewable materials, such as spinach leaf bioscreen. This study aims to determine the effect of Amaranthus tricolor L red spinach leaves as an anti-radiation bioscreen on laptops. This study uses a pre-experimental method with a one group pre-test post-test design. The amount of electromagnetic radiation was measured using an electromagnetic radiation detector DT-1130. Data analysis used correlation test and simple linear regression test. The results of the Pearson product moment analysis obtained a correlation coefficient value of r = -0.999 which means that there is a very strong relationship between the increase in the number of spinach leaves and the decrease in laptop radiation. Regression test shows the amount of radiation (y) can be predicted from the number of leaves (x) with the equation y=1420,106–26,311x, meaning that an increase in the use of spinach leaves by 1cm2 will reduce radiation by 26,311µW. The results of this study indicate that spinach leaves have the potential as a bioscreen material in reducing exposure to electromagnetic radiation on laptops.